2021
DOI: 10.7150/ijms.60962
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Successful Responses to Ganglion Impar Block: A Retrospective Study

Abstract: Background:The ganglion impar (ganglion of Walther) block has been used to manage coccygeal and perineal (perianal and genital) pain due to both benign and malignant causes. However, the factors associated with successful responses to ganglion impar block are unknown. Therefore, in the present study, we aimed to identify the independent factors associated with successful responses to ganglion impar block in patients with chronic pain in coccygeal and perineal regions. Methods: From January 2008 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…Gündüz et al 8 achieved >50% pain reduction with GIB in 18 of 19 patients with traumatic coccidynia. Kim et al 9 reported a VAS score reduction of >4 units with GIB in 17% of patients with non‐cancer‐related coccyx pain. This study found at least a 50% improvement in VAS score in 56% of patients with coccydynia at 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Gündüz et al 8 achieved >50% pain reduction with GIB in 18 of 19 patients with traumatic coccidynia. Kim et al 9 reported a VAS score reduction of >4 units with GIB in 17% of patients with non‐cancer‐related coccyx pain. This study found at least a 50% improvement in VAS score in 56% of patients with coccydynia at 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Although GIB has been reported to be an effective and reliable treatment for coccygodynia, there are limited studies6 10 evaluating the predictive factors for treatment response. In a retrospective study, Sencan et al 6 performed dynamic radiographic evaluations on 37 patients and examined the effect of coccygeal dynamic pattern on GIB.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 102 patients, Kim et al 10 reported that demographic data, including age, sex, and BMI, had no impact on the treatment success. Sencan et al 6 also noted no correlation between treatment success and age, sex, and BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations